TINDAK PIDANA MELAKUKAN PERSETUBUHAN DENGAN SENGAJA PADA ANAK (PUTUSAN NOMOR 410/PID.SUS/2022/PN.JKT.TIM): The Crime of Intentional Contract With A Child (Verdict Number 410/Pid.Sus/2022/PN.Jkt.Tim) - Cindy Hardiyanti Wibowo; Vience Ratna Multiwijaya (Faculty of Law, Universitas Trisakti, 2025)
The crime of committing intercourse intentionally on children is an act committed by an adult male with a girl aged 14 (fourteen) years, and by the judge decided based on Article 81 paragraph (2) jo Article 76 D of Law Number 35 Year 2014 Study of Decision Number 410/Pid.Sus/2022/PN.JKT. The team with the subject matter appointed is: whether the application of criminal imposition by the judge is appropriate or not based on Article 81 paragraph (2) jo Article 76 d Law Number 35 Year 2014?. This study uses normative legal research in its analytical descriptive, using secondary data through library studies and using qualitative methods processed to obtain conclusions in this study, namely: The application of criminal offenses given by the panel of judges is not appropriate based on Article 81 paragraph (2) jo Article 76 D Law Number. 35 of 2014 concerning Child Protection. The results of this act of this act should be handed down in Article 81 paragraph (1) jo Article 76 D of Law Number 35 of 2014, because it was done like the same joy.